1992
DOI: 10.1055/s-2008-1080395
|View full text |Cite
|
Sign up to set email alerts
|

The Latham Technique: Contemporary Presurgical Orthopedics for the Complete Oral Cleft Technique and Preliminary Evaluation — A Bone Marker Study

Abstract: The Latham technique is the initial interventional procedure used to treat the facial orthopedic problems found in unilateral cleft lip and palate (UCLP) and bilateral complete cleft lip and palate (BCLP) patients. In UCLP and RCLP deformities, the soft tissue and basal abnormalities have a recognizable pattern of deformity defined by excess or deficiency in anatomic form, position, or direction within the craniofacial milieu. The Latham appliance applies controlled directional forces to reposition the displac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…The superior orbital rims used for reformatting have less precision and accuracy (Baumrind and Frantz, 1971) compared to bone marker landmarks (Spolyar et al, 1992). Yet, in Table 1C, the bilateral vertical translations were, as expected, equal (0.8 / 0.9 mm) indicating a valid reformatting process.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The superior orbital rims used for reformatting have less precision and accuracy (Baumrind and Frantz, 1971) compared to bone marker landmarks (Spolyar et al, 1992). Yet, in Table 1C, the bilateral vertical translations were, as expected, equal (0.8 / 0.9 mm) indicating a valid reformatting process.…”
Section: Discussionmentioning
confidence: 98%
“…Notwithstanding, other UCLP occlusion studies with either passive PSIO and sequential primary bone grafting (Hathaway et al, 1999) or active Latham PSIO without primary alveolar surgery (Chan et al, 2003) showed both protocols achieved dental arch relationships in preadolescence like children without PSIO intervention nor alveolar grafting. Finally, active Latham PSIO treatment categorically shifts the native growth-compensated developmental derangement while normalizing cleft component positions (Spolyar et al, 1992). In a UCLP cast study, larger cleft width (derangement) in infancy between cuspid points was significantly associated with less anterior and posterior dental crossbite at age 5 years (Reiser et al, 2010); would that the native growth-compensated developmental derangement having been normalized by PSIO, then lead to more crossbites?…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 98%
“…With this shorter treatment course, the “modified Latham” appliance allows operative placement of the device at an older age, while still facilitating correction of the cleft lip between 3 and 4 months of age (Spolyar et al, 1992; Nahai et al, 2005; Hammoudeh et al, 2017). In our series, the “modified Latham” appliance was inserted at an average age of 3.80 months of age.…”
Section: Discussionmentioning
confidence: 99%
“…Anchors were needed and were supplied via 4 fixation screws into the hard palate (KLS Martin, Tuttlingen, Germany). Fixation screws were placed under general anesthesia in the same locations that pins of the Latham appliance were located (Spolyar et al, 1992; Figure 2B). This location was selected to avoid tooth germs and provide reliable stabilization.…”
Section: Case Reportmentioning
confidence: 99%